Allied special forces and prisoner of war recovery operations in Europe, 1944-1945 - Wylie, Neville (Society for Military History, 2017)
This article investigates the efforts made to protect prisoners of war (POWs) in German hands at the end of the Second World War. Challenging contemporary and historical judgments, it argues that Allied plans were reasonable, realistic, and reflected a widespread belief in the importance of protecting the lives and well-being of Allied POWs. Although only two operations were ultimately mounted, the process of raising and equipping specialized recovery units provided a valuable learning experience for Allied planners, which later went on inform recovery operations in the Pacific, and set a precedent that arguably extends to influence attitudes towards POW recovery today.